Effectiveness of different SSRI antidepressants in combination with CBT for short-term management of panic disorder - Md. Zain, Azhar; Naing, Khin Ohnmar@Noor Jan (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2007)
Objective: This paper reports the result of an analysis of data of brief therapy for out-patients with panic disorder referred by physicians in a busy specialist hospital in Kuala Lumpur. Methods: The patients were randomly assigned into different groups of SSRI (Specific Serotonin Reuptake Inhibitor) antidepressants i.e. escitalopram, sertraline, or fluoxetine. All patients received cognitive behaviour therapy (CBT). The therapy was aimed for a maximum of twelve sessions. There were 33 patients in the escitalopram group, 31 patients in the sertraline group, and 31 patients in the fluoxetine group. Results: The result shows that all the groups were similar in the severity and scores for pre-treatment but for post-treatment, there were significant differences among them. Conclusion: All groups showed significant improvements in all modalities of measurements. However, the escitalopram and sertraline groups showed faster overall improvement compared to the fluoxetine group.